1999
DOI: 10.1097/00005392-199903000-00012
|View full text |Cite
|
Sign up to set email alerts
|

CORRELATION AND PROGNOSTIC SIGNIFICANCE OF p53, p21WAF1/CIP1 AND Ki-67 EXPRESSION IN PATIENTS WITH SUPERFICIAL BLADDER TUMORS TREATED WITH BACILLUS CALMETTE-GUERIN INTRAVESICAL THERAPY

Abstract: Our results indicate that p21WAF-1-CIP1 seems to be regulated by p53 independent pathways in superficial bladder cancer. The present study did not indicate an independent prognostic significance in patients treated with BCG for p53, p21WAF-1-CIP1 or Ki-67 markers. Larger prospective studies are needed to evaluate further the independent value of these biological markers in superficial bladder cancer management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
2
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 16 publications
5
32
2
1
Order By: Relevance
“…In this aspect, our results are consistent with those included in other multivariate studies, in terms of survival, 6,12,19,21 recurrence, 8,11,[15][16][17][18][19]25 and progression. [21][22][23]25 Our study shows that there are several significant variables in the prognosis of bladder TCC at T1 and T2a classifications. The expression of p53 shows its independence in predicting survival, progression, and metastasis development, whereas tumor multifocality, the T2a classification, and the presence of CIS in random bladder biopsy are the variables associated with a greater risk of recurrence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this aspect, our results are consistent with those included in other multivariate studies, in terms of survival, 6,12,19,21 recurrence, 8,11,[15][16][17][18][19]25 and progression. [21][22][23]25 Our study shows that there are several significant variables in the prognosis of bladder TCC at T1 and T2a classifications. The expression of p53 shows its independence in predicting survival, progression, and metastasis development, whereas tumor multifocality, the T2a classification, and the presence of CIS in random bladder biopsy are the variables associated with a greater risk of recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…If we consider our results and those of other authors such as Zlotta et al 25 and Pfister et al, 8 in which the expression of Ki-67 does not appear as an independent variable of recurrence, it would seem that the expression of Ki-67 does not play an important role in predicting tumor recurrence.…”
Section: Discussionsupporting
confidence: 55%
“…However, the expression status and biologic or prognostic significance of the caspase and IAP family proteins in urothelial neoplasms is not clear. In the present study, we first systematically evaluated the expression profile of the major apoptosis regulators, including caspases (CASP3,6,7,8,9,10,and 14), IAPs (survivin/BIRC5, CIAP1, CIAP2, XIAP, and LIVIN), APAF1, SMAC, and BCL2, as well as proliferation markers Ki67 and PHH3, in Ta/T1 human urinary bladder urothelial carcinomas and normal urothelium samples by immunohistochemistry. The analysis showed that survivin/ BIRC5 nuclear labeling index (BIRC5-N), but not cytoplasmic staining, was the only apoptotic marker which correlated significantly with tumor grade, stage, and patient outcome.…”
mentioning
confidence: 99%
“…34 However, systematic evaluation of the expression profile and biologic significance of these apoptosis regulators in urothelial carcinomas is lacking. In addition, although tumor cell proliferation (as assessed by the immunomarker MIB1/Ki67) has been correlated with urothelial carcinoma progression and patient survival, 4,11,14,17,21,25 the relationship of proliferation activity with caspase and IAP expression in urothelial carcinomas is not clear.…”
mentioning
confidence: 99%
“…This indicated that an increased level of expression of p21 WAF1 does not correlate with its cell cycle arrest function and may have some other function (s). In this context, elevated levels of p21 WAF1 expression have been detected in gliomas [41], non small cell lung carcinomas [21], [42], invasive cervical cancer [43] and bladder carcinomas [44]. A 50-100 fold increase in p21 WAF1 expression has been detected in NIH 3T3 cells transformed with activated Ras oncogene [20].…”
Section: Nih 3t3/mot-2 Cells Show An Upregulation Of P21waf1 Expressionmentioning
confidence: 99%